Pre-operative rehabilitation in reducing post operative pain - Kanagarathinam, Siva Subramanian; Devakumar, Satish Murugesan; Inbasekaran, Anbarasu; Urabinhatti, Kiran Arjun; Umesh, Rohan N.; Naik, R. K. Hanumantha; Thangasamy, Selvaraj; Sathyanesan, Jeswanth (International Surgery Journal, 2023)
Background: Prehabilitation is the process of improving the functional reserve of the patient. It is being a new paradigm increasingly being applied in recent days for all types of surgeries. The postoperative outcome of the patient is being affected if their functional reserve is low. It induces major complications, reduced ambulation and higher respiratory and wound related complications. One of the major factors in reducing the mobility of the patient is postoperative pain following surgery. Many studies are being done in assessing the effectiveness of prehabilitation in improving the postoperative outcome of the patients. We have done a study to evaluate the efficacy of the prehabilitation in relation to the postoperative pain score in pancreatic surgery and its outcome. Methods: To study the effect of prehabilitation over the postoperative pain score. All patients related to benign and malignant disorders of pancreas who were subjected to surgery were taken in to study. The nutritional regimen, additional protein intake and their physical activity along with their preoperative Metabolic equivalents were taken in to study. All patients were studied for their postoperative pain score and data generated comparing their preoperative workup with postoperative pain scale. Results: The higher metabolic equivalents had a higher significant value relating to their pain scale. The distance covered in a day also influenced the postoperative pain. About the protein intake it was shown that additional protein intake in the preoperative period has shown a significant impact on the postoperative pain scale. Conclusions: From this little cohort group it cannot be generalised but In relation to the prehabilitory measures for pancreas related surgery in our surgical gastroenterology department. It is shown that preoperataive additional protein intake and their physical activity especially their metabolic equivalents prior to surgery had a good relation to their pain scale showing a positive correlation between them.